Julietta Singh. Unthinking Mastery: Dehumanism and Decolonial Entanglements. Duke UP, 2018. - Michael Mulvey (Studies in 20th & 21st Century Literature, 2018)
Review of Julietta Singh. Unthinking Mastery: Dehumanism and Decolonial Entanglements. Duke UP, 2018. xi + 216pp.
Keywords: Unthinking Mastery; Singh